The Relationship of Personality Type in Early Adolescents and Bullying Behavior in Students at SMP Negeri 1 Gedangan Sidoarjo - nurhayati, Ceria; Diajeng Ayu, Hernindya; Saidah, Qori’Ila (Universitas Nahdlatul Ulama Surabaya, 2025)
Many teenagers do bullying act on their peers without thinking about the consequences of their effects. If this continues, it can make teenagers who are victims of bullying behaviour become insecure and can even withdraw from the surrounding environment. The role of health workers as educators is to educate about the dangers of bullying behavior. This study uses an analytic observational design with a cross-sectional approach. In this study the instrument used was the demographic questionnaire, the Free MTBI Personality Test questionnaire to provide a brief description of personality types, and the Adolescent Peer Relations Instrument (APRI) questionnaire to assess bullying behavior that would be distributed to adolescents of class VII and VIII as many as 235 respondents using Probability Sampling technique with a statified random sampling approach. This research was conducted through Google form due to the current pandemic conditions which made it impossible to conduct research directly. At the beginning of the Google form page, an informed consent will be used which is used as approval to become a prospective subject. The results showed that most of the adolescents had 183 extrovert personality types (77.9%) and the majority of mild bullying behaviors were 204 people (84.8%) Spearman Rho Test showed that the value of r = 0,401 with a value of ρ = 0,000 (ρ <α = 0,05) ie there is a moderate relationship between adolescent personality types with bullying behavior.